CARACTERÍSTICAS FITOSSOCIOLÓGICAS DA ARBORIZAÇÃO VIÁRIA DE BONITO-MS - Zamproni, Kendra; Biondi, Daniela; Maria, Tamara Ribeiro Botelho de Carvalho; Bobrowski, Rogério (Revista da Sociedade Brasileira de Arborização Urbana, 2019)
Diagnosis through the street trees’ assessment is fundamental to the planning and maintenance of this asset, in order to maximize the benefits provided by the urban trees. Phytosociological studies allow an improvement of the data analysis obtained from the inventory, however they are still not used often in research on this subject. Within this context, the objective of this study was to analyze the phytosociological characteristics of the street trees of Bonito-MS, from the data obtained through a previous urban forest inventory. For this, the following factors were analyzed: frequency, density, dominance (expressed by the crown area in replace of the DBH) and importance value, calculated by the traditional method and by the Species Performance Index (IPE). Within the results, it is possible to verify that the importance value highlighted species which presented larger crown area even to the detriment of those that presented higher absolute frequency. The species with the highest frequency, density and dominance values was Licania tomentosa, and, despite the homogeneity of its planting in the municipality, this species presented high IPE value. The use of these phytosociological parameters allows a better evaluation of the adaptation and performance of the species in the municipality and assists in the decision-making of new plantings.